Steady-state Analysis of Doubly-fed Wind Power Generator - 郁灿; 金新民; 张禄; 战亮宇 (Kongzhi Yu Xinxi Jishu)
It introduces the steady-state analysis of doubly-fed wind power generator based on the work conditions and the equivalent circuit, reckons the calculation process of the current on both stator side and rotor side. Then, under the known rated parameters of the generator, energy and current on the stator side and rotor side are calculated with full power. The steady-state analysis of the generator is also simulated. At last, it is verified the correctness of the theoretical analysis based on the experimental current waveforms under the full power generation of doubly-fed wind power generator.